Influence of red and white led lamps on the productive performance and egg quality of commercial laying hens - Larissa Faria Silveira Moreira; Lázaro Luan Miguel; Maria Isabel Ferreira Santos; Javer Alves Vieira Filho; Rosiane de Souza Camargos; Luiz Carlos Machado; Adriano Geraldo (Acta Scientiarum. Animal Sciences, 2024)
This study aimed to evaluate the effectiveness of different LED lamp colors (red and white) on the productive performance and egg quality of light laying hens. A total of 144 birds of the commercial strain Hy-Line® W-36 aged 44 weeks were distributed in a completely randomized design with two treatments (red and white LEDs) and 12 replicates, totaling 24 experimental plots with six birds each. Treatment means were compared by the F Test (5% probability) on the statistical software SISVAR. This study found that laying hens under red LED lamps showed a trend of greater egg production bird-1 day-1 (%) (p = 0.084), average egg weight (g) (p = 0.0826), egg mass (p < 0.05), and shell thickness (mm) and height (mm) (p < 0.01), whereas birds under white LED light showed better yolk color (p < 0.05). It is concluded that red LED illumination increases egg production and quality in light laying hens.